Immunosuppressive Drugs and COVID-19: A Review - Schoot, Tessa S.; Kerckhoffs, Angèle P. M.; Hilbrands, Luuk B.; van Marum, Rob J. (Frontiers in Pharmacology, 2020)
Background: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is currently unknown whether immunosuppressive drugs are advantageous or detrimental in patients with COVID-19. Immunosuppressive drugs could be harmful in the initial phase of COVID-19. In this phase, the host immune response is necessary to inhibit viral replication. However, immunosuppressive drugs might have a beneficial effect in the later, more severe phase of COVID-19. In this phase, an overshoot of the host immune response (the “cytokine storm”) can cause ARDS, multiorgan failure and mortality. Aim: To summarize the available evidence on the effect of immunosuppressive drugs on infection with SARS-CoV-2. The effects of immunosuppressive drugs on similar pandemic coronaviruses may resemble the effects on SARS-CoV-2. Thus, we also included studies on the severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) Methods: The study protocol was registered in PROSPERO (registration number CRD42020181137). We included randomized controlled trials (RCTs), cohort studies with a control group and case-control studies concerning humans ≥ 18 years old. We also included in-vitro studies and animal studies with a control group. Results and conclusion: 69 studies were included. Interestingly, MPA inhibits SARS-CoV-2 replication in-vitro. Clinical studies are needed to confirm the inhibitory effect of MPA on SARS-CoV-2 replication in-vivo. There are indications that corticosteroids and IL-6 inhibitors, like tocilizumab, can reduce mortality and prevent mechanical ventilation in patients with COVID-19. However, observational studies have contradictory results and the risk of bias is high. Thus, these results have to be confirmed in high-quality clinical trials before these drugs can be implemented as standard care. Based on the positive results of CNIs, mTOR inhibitors and thiopurine analogues in in-vitro studies with SARS-CoV and MERS-CoV, it would be interesting to investigate their effects on SARS-CoV-2 replication.